Analysis of factors hindering effective teaching and learning of business studies in secondary schools in Gwanda district - Dzichauya, Talent (Midlands State University, 2019)
This study sought to analyse the factors hindering effective teaching and learning of Business Studies in secondary schools in Gwanda district. The objectives of the study were to identify and analyse the administrative, teacher and student related challenges hindering the learning and teaching of Business Studies at Ordinary and Advanced Level and to suggest ways of addressing the challenges available in the teaching and learning of Business Studies. A descriptive research design was used in conducting this research. Only primary data sources on the experiences and views of the school administrators, teachers and students on teaching and learning Business Studies was collected and used. Purposive sampling was used to initially select a sample 5 schools out of a total of 13 secondary schools in Gwanda district from which respective administrators and teachers of the 5 schools were investigated and 30% of their respective students. The survey method, by way of self-administered questionnaires was used to collect data from the respondents. The Statistical Package for Social Sciences (SPSS) version 23 was used to input collected raw data, process and generate descriptive statistics for presentation and analysis. The research showed that administrative related factors including inadequate modern infrastructure resources that support teaching and learning, non-existence of business units or income generating projects for practical component of learning, absence of budgets and programmes for participation in academic seminars and lax teacher and student assessment; and teacher related factors including lack of motivation due to low remuneration and incentives and inadequate research facilities and non-participation in refresher courses for teacher upgrade; and student negative attitude on the subject and lack of self-drive hinders performance of teachers and students in Business Studies in schools. This study recommends that school authorities prioritising acquiring and installing modern school infrastructure resources that support teaching and learning, availing of budgets and programmes for academic seminars and staff refresher courses and establishment of business units at schools for practical learning. It is also recommended that government and local communities design packages for motivating teachers and providing students with induction on learning for transformation change. Finally, the study recommends further research on the relationship between learning business studies and starting and running own small business unit; and on the impact of teaching for transformation change on students conduct.